Different Deeds, Different Needs—Types of Violence Against Women and Social Support Sought Online - Tinkara Pavšič Mrevlje; Vanja Ida Erčulj (Behavioral Sciences)
Women, as victims of violence, among which intimate partner violence prevails, venture online to seek a supportive community. Members of online support groups differ in the experiences and needs they have and support they seek. The objective of this research was to explore the difference in types of support sought and support received between women who self-report having been a witness/victim of violence and others who directly ask for help without explaining their circumstances. For this purpose, content analysis of 600 randomly selected starting posts from an online support community was performed. The results reveal an association between the needs expressed and the experience of violence described. Although users most frequently sought informational support, those recounting sexual violence more often asked for emotional support or were looking for an emotional release. Posts describing a different kind of violence were more likely to bring more support than short posts directly asking for help. The findings are important since women in a violent relationship tend to become more isolated or controlled by their partners, pointing to the crucial role of online support in helping and encouraging those women to take the first step in seeking help from formal institutions.